Intervention Program to Improve Grief-Related Symptoms in Caregivers of Patients Diagnosed With Dementia - Bravo-Benítez, Jorge; Cruz-Quintana, Francisco; Fernández-Alcántara, Manuel; Pérez-Marfil, María Nieves (Frontiers in Psychology, 2021)
The objectives of the present study were to adapt a grief intervention program to family caregivers of patients with dementia, and assess its effectiveness in improving the symptoms of grief and other health-related variables. The intervention was based on Shear and Bloom’s grief intervention program, with the necessary adaptations for use in the grieving process for a family member’s illness. A total of 52 family caregivers of individuals with dementia participated. They were evaluated using a battery of self-report measures assessing grief, overload, resilience, post-traumatic growth, experiential avoidance, health-related quality of life, and benefits of care. The results suggest that the program is effective in improving grief symptoms, caregiver burden, resilience, post-traumatic growth and quality of life of family caregivers. It is necessary to create and implement interventions targeting caregivers’ feelings and manifestations of ambiguous grief, because there is a lack of programs providing an efficient solution for the mental and physical health of caregivers, and because of the human and socioeconomic cost involved in neglecting this group.